2021
DOI: 10.1038/s41419-021-04095-8
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0003222 accelerates stemness and progression of non-small cell lung cancer by sponging miR-527

Abstract: The relationship between circular RNA (circRNA) and cancer stem cells (CSCs) is uncertain. We have investigated the combined influence of CSCs, circRNA (hsa_circ_0003222), and immune checkpoint inhibitors in NSCLC progression and therapy resistance. We constructed lung CSCs (LCSCs; PC9 and A549). The effects of hsa_circ_0003222 in vitro were determined by cell counting, colony and sphere formation, and Transwell assays. A tumor xenograft model of metastasis and orthotopic model were built for in vivo analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Our data suggested that miR-527 is a target miRNA of circ_0138959 and could be upregulated by inhibition of circ_0138959. miR-527 is a newly discovered tumor suppressor in non-small cell lung cancer (NSCLC), bladder cancer, and glioma [ 45–47 ]. However, there are almost no reports of miR-527 in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that miR-527 is a target miRNA of circ_0138959 and could be upregulated by inhibition of circ_0138959. miR-527 is a newly discovered tumor suppressor in non-small cell lung cancer (NSCLC), bladder cancer, and glioma [ 45–47 ]. However, there are almost no reports of miR-527 in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired resistance induced by the TME primarily acts as an adaptive response by the host towards pharmacological damage (36). Li et al explored the combined effects of cancer stem cells (CSCs), circRNA (hsa_circ_0003222), and immune checkpoint blockers in NSCLC malignant behavior as well as drug resistance and found that NSCLC resistance to anti-PD-L1-based therapy could be reduced by silencing hsa_circ_0003222 (37). Additionally, circFGFR1 promotes immune evasion of NSCLC cells and enhances tolerance to anti-PD-1-based therapy by interacting with miR-381-3p and upregulating the expression of C-X-C motif chemokine receptor 4 (CXCR4) (38).…”
Section: Tmementioning
confidence: 99%
“…suggested that tumor-derived exosomal circRNA_102481 participated in EGFR-TKI resistance by sponging microRNA-30a-5p to modulate ROR1 in NSCLC ( 82 ). As for immune checkpoint inhibitors, hsa_circ_0003222 and circFGFR1 can promote NSCLC resistance to anti-PD-L1-based and anti-PD-1-based therapies, respectively ( 37 , 38 ). Furthermore, suppression of circIGF2BP3/PKP3 promotes the therapeutic efficacy of anti-PD-1 in a Lewis LADC mouse model ( 39 ).…”
Section: Circrnas and Drug Resistancementioning
confidence: 99%
“…Many circular RNAs have been discovered to be biomarkers that impact the onset and growth of malignancies in recent years, attracting a lot of attention. They have been identified in lung cancer ( 6 ), hepatocellular carcinoma ( 7 ), gastric cancer ( 8 ), colorectal cancer ( 9 ), and so on. However, the molecular mechanisms and early diagnosis of cancer are not well understood.…”
Section: Introductionmentioning
confidence: 99%